Development of Wire Cable Drive for Kioriz SP850A 4WD Engine to Improve Agricultural Productivity - Muhammad Ilham Abdillah; Setuju Setuju; Widodo Widodo; Alfat Khaharsyah; Heri Kurnianta (VANOS Journal of Mechanical Engineering Education, 2026)
This study aims to develop an alternative Bowden cable for the Kioritz SP850A 4WD agricultural machine to address issues of high cost, long delivery times, and limited availability of original equipment manufacturer (OEM) cables. The research adopted a Research and Development (R&D) design, which emphasizes systematic product development through stages of needs identification, design, prototype fabrication, testing, and evaluation. Within the testing and evaluation stages, experimental research methods were applied to assess the mechanical and economic performance of the developed cable. The alternative cable was manufactured using SAE 1065 steel subjected to tempering heat treatments at 300°C, 400°C, and 500°C. Mechanical testing included tensile strength, hardness, elongation, and fatigue life, supported by statistical analysis using ANOVA and regression, as well as economic analysis. The results indicate that tempering temperature significantly influences mechanical properties, with the 300°C condition producing the highest tensile strength (1848.7 MPa) but increased brittleness, while the 400°C condition achieved the most balanced performance, including tensile strength of 1651.5 MPa, hardness of 50.2 HRC, and fatigue life comparable to OEM cables. Economic evaluation demonstrated cost savings of ¥295,850 per case, an ROI of 639.6%, and a payback period of 1.7 months. These findings confirm that the developed alternative Bowden cable is both technically and economically feasible, offering a practical solution to reduce machine downtime and enhance agricultural productivity.